PURWARUPA SISTEM RUMAH PINTAR PURWARUPA SISTEM RUMAH PINTAR BERBASIS INTERNET OF THINGS: PURWARUPA SISTEM RUMAH PINTAR BERBASIS INTERNET OF THINGS - Agustian Noor; Murad Maulana; Arif Supriyanto (LPPM STMIK Lombok, 2022)
A smart house is a house that can provide comfort and a sense of security to the residents in it, a smart home is one application of the use of advanced technology. The development of this smart home system prototype aims to provide an overview of implementation, comfort, security, and convenience when the home uses a smart home, this smart home prototype uses an android application as a medium for controlling electronic devices. Users have access to control electronic devices and also monitor temperature, humidity, smoke, LPG gas, and carbon gas. The problems that exist in ordinary homes that do not apply smart home technology are the lack of security at home, and the wasteful use of electricity when forgetting to turn off electronic devices, therefore this system was created to solve these problems. In the development of this system the author uses the waterfall model, the programming language used is C language, and uses Block diagrams for its design.